STUDI PERENCANAAN DAN PENGELOLAAN BANGUNAN SARANA AIR BERSIH BERBASIS PARTISIPASI MASYARAKAT DI DESA PAYA BEKE - Ziana Ziana; Suhendrayatna Suhendrayatna; Mulyadi Mulyadi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Planning and building of water supply in rural areas aimed at helping rural communities who do not have access to adequate clean water especially medium to lower income people. Not all communities in the District of Reparation Nara have clean water in their homes - each, the tough get clean water every day and spend the time to get their water through the trail and winding road to get to the water source. Based on these problems, this study aimed to complement the building plan of clean water that can be distributed to neighborhood residents with community participation in the management and in maintenance. The study was conducted by calculating the water needs of the people and community participation in the management of water supply through the distribution of questionnaires (questionnaire) contains several questions relating to the need for clean water. This method is done by descriptive surveys with making analytical processing of data in terms of percentage in the form of a bar chart to make a conclusion. The results showed that through the design of the building is the public water supply already has a concept to build a clean water future. The results of the questionnaire showed people are looking forward to construction of water supply, and is ready to support the development and management. The study design of buildings generate clean water to meet the needs of clean water for the village of Paya Beke with and management by promoting community involvement in both systems management and maintenance ongoing basis.